Functional feeding response of Nordic and Arctic krill on natural phytoplankton and zooplankton. (26th March 2020) - Cabrol, Jory; Fabre, Anaïs; Nozais, Christian; Tremblay, Réjean; Starr, Michel; Plourde, Stéphane; Winkler, Gesche
Abstract: Krill species play a pivotal role in energetic transfer from lower to upper trophic levels. However, functional feeding responses, which determine how food availability influences ingestion rates, are still not well defined for northern krill species. Here, we estimated and compared the functional feeding responses on natural communities of phytoplankton and mesozooplankton of two coexisting species, Meganyctiphanes norvegica and Thysanoessa raschii . We tested the influence of the presence of phytoplankton on the ingestion rate and the selectivity of both krill species when feeding on zooplankton prey. We performed a series of feeding experiments using increasing concentrations of natural phytoplankton (64 taxa; 2 to >50 μm) and mesozooplankton (28 taxa; ~100–2000 μm) assemblages and the latter in presence and absence of phytoplankton. Results revealed that both krill species exhibited a Holling type III feeding response on phytoplankton. However, T. raschii was able to exploit efficiently the highest phytoplankton concentrations. Our experiments highlighted that the presence of phytoplankton modified the functional feeding response on mesozooplankton preys of M. norvegica, but not that of T. raschii . Similarly, the presence of phytoplankton influenced the feeding selectivity on mesozooplankton preys, although both species showed contrasting selectivity patterns. In addition, we estimated the energy needs in relation to the daily rations. T. raschii satisfied its energy needs by feeding either on high phytoplankton concentrations or on low mesozooplankton densities, whereas M. norvegica did not cover its metabolic costs efficiently by feeding on phytoplankton only, even at high phytoplankton concentrations.